Crohn's disease: integrative aspects from diagnosis to treatment (Research, Society and Development, 2023)
Objective: To identify current aspects throughout the course of Crohn's disease, from diagnosis, pharmacological and surgical treatments and nutritional recommendations. Method: This study is an integrative literature review based on the search for papers in databases, Pub Med, Lilacs, Scielo, Periodicals and websites, with the following descriptors in “Crohn's disease”, “Crohn's disease symptons”, “Crohn's Disease treatment”, “Inflammatory Bowel Diseases”, “Physiopathology of Inflammation”, using original research articles and reviews from 1990 to 2022. This bibliographic survey was carried out in the period of 03/01/2022 to 10/20/2022. Results: 1850 articles were found and, after using the inclusion criteria, 84 studies were selected. Discussion: Currently, the entire course of Crohn's disease is very complete, from diagnosis to treatment, which may involve biological drugs, in addition to the need for an adequate diet in order to avoid malnutrition in the patient. Conclusion: Considering all the complexity encompassed in Crohn's disease, the performance of a multidisciplinary team in the conduct of the patient's treatment is essential, which can contribute immensely to the patient's quality of life and adherence to treatment.